1990
DOI: 10.1093/hsw/15.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Families as Educational Consumers: What Do They Want? What Do They Receive?

Abstract: In this study of 100 families of patients diagnosed with psychiatric disorders, the authors sought to discover what kinds of help families as educational consumers wanted, whether the desired help was received, and where they got (or hoped to get) help. One-half of the families wished they had received more assistance. Most wanted information from psychiatrists, and their level of education was an important factor in determining whether they actually saw psychiatrists. The families felt a need for professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…For example, consistent with the findings of Thompson and Weisberg (1990), educational level was significantly related to several topics of interest. Also, findings of differences in educational interests based on diagnosis (paraplegia vs. quadriplegia) were consistent with those of Mueser et al (1992), which demonstrated significant dBerences in interests between individuals with schizophrenia and those with affective disorder.…”
Section: Discussionsupporting
confidence: 87%
“…For example, consistent with the findings of Thompson and Weisberg (1990), educational level was significantly related to several topics of interest. Also, findings of differences in educational interests based on diagnosis (paraplegia vs. quadriplegia) were consistent with those of Mueser et al (1992), which demonstrated significant dBerences in interests between individuals with schizophrenia and those with affective disorder.…”
Section: Discussionsupporting
confidence: 87%
“…One potential reason for the low participation in family psychoeducation may be that services do not appropriately target the differing needs and preferences of family members and consumers (13)(14)(15). Family member characteristics-such as phase of life or age (13,(16)(17)(18), gender or relationship to the ill relative (19,20), ethnicity (21,22), and experiences of stigma (5,12,23,24)-and consumer characteristics-such as contact with family (6,22), diagnosis (25), duration of mental illness (26)(27)(28)(29), and severity of mental illness (30)-may influence family need. Family member characteristics-such as phase of life or age (13,(16)(17)(18), gender or relationship to the ill relative (19,20), ethnicity (21,22), and experiences of stigma (5,12,23,24)-and consumer characteristics-such as contact with family (6,22), diagnosis (25), duration of mental illness (26)(27)(28)(29), and severity of mental illness (30)-may influence family need.…”
mentioning
confidence: 99%
“…Furthermore these unmet learning needs are correlated with less successful treatment outcomes (Thompson & Weisberg, 1990). For example, studies of what clients with psychiatric disorders want have identified their unmet needs as "educational consumers."…”
Section: Education From the Client's Perspectivementioning
confidence: 99%